Analisis Pidana Kerja Sosial Sebagai Alternatif Pidana Jangka Pendek : Perspektif KUHP Baru Indonesia - Taufiq Akbar Al Falah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the implementation of community service as an alternative short-term punishment in the context of the reform of Indonesian criminal law through Law Number 1 of 2023 on the Criminal Code (KUHP). Criminal law reform is necessary to address issues such as the overcapacity of correctional facilities and the need for adaptive legal frameworks. Using a prescriptive normative approach, this research identifies the philosophical, legal, and sociological foundations underlying the implementation of community service. The findings indicate that the application of community service aligns with the principles of restorative justice, legal effectiveness, and the social reintegration of offenders. These findings support the idea that community service can be a humane, efficient, and beneficial alternative for society.